The effects of painless nerve growth factor on human microglia polarization - Lisi, Lucia; Marinelli, Silvia; Ciotti, Gabriella Maria Pia; Pizzoferrato, Michela; Palmerio, Federica; Chiavari, Marta; Cattaneo, Antonino; Navarra, Pierluigi (Frontiers in Cellular Neuroscience, 2022)
Previous studies in the rat suggest that microglial cells represent a potential druggable target for NGF in the brain. The painless human Nerve Growth Factor (hNGFp) is a recombinant mutated form of hNGF that shows identical neurotrophic and neuroprotective properties of wild-type NGF but displays at least 10-fold lower algogenic activity. From the pharmacological point of view, hNGFp is a biased TrkA agonist and displays a significantly lower affinity for the p75NTR. This study aimed to evaluate the expression of TrkA and p75NTR NGF receptors in two different human microglia cell lines, and to investigate the effects of hNGFp and wild-type NGF (NGF) on L-arginine metabolism, taken as a marker of microglia polarization. Both NGF receptors are expressed in human microglia cell lines and are effective in transducing signals triggered by NGF and hNGFp. The latter and, to a lesser extent, NGF inhibit cytokine-stimulated iNOS expression and NO production in these cells. Conversely NGF but not hNGFp stimulates arginase-mediated urea production.